Building Confidence and Fluency in English through Drama-based Learning - Dewi, Arsita Maharani Kusuma; Hayati, Rita (Journal of English Language and Education, 2025)
This study investigates the impact of drama-based activities on enhancing students’ confidence, fluency, and speaking skills in an English Literature in ELT course. The research was conducted among sixth-semester students of the English Education program using a qualitative method. The data were collected through questionnaire and semi-structured interview. The findings revealed that the integration of drama activities significantly contributed to students’ speaking performance by creating an engaging and expressive learning environment. It also boosted their self-confidence and reduced their speaking anxiety. This study suggests that incorporating drama into ELT classrooms can be a powerful pedagogical tool for language development.